SISTEM PENGATUR SUHU AIR OTOMATI SISTEM PENGATUR SUHU AIR OTOMATIS MENGGUNAKAN METODE PROTOTYPE BERBASIS IOT PADA BUDIDAYA IKAN HIAS AIR TAWAR ANNAS GUPPY - Raihan Asabumi; Bambang Wisnu Widagdo (PT Triputra Sejahtera Prima, 2024)
Ornamental fish have become a hobby and also a promising and profitable side business opportunity, one of which is the Gupi fish (Poecillia reticulata), this fish can be easily reproduced and is suitable as an additional business for hobbyists. However, cultivating guppy fish is not easy because sudden changes in temperature have a big impact on the health and metabolism of cultivated fish. This information was obtained during an interview with the owner of the ANNAS GUPPY ornamental fish farm. The author has developed a prototype of a more accurate and efficient water temperature control system based on Arduino. Research was also carried out to integrate a water temperature control system with internet of things (IoT) technology to enable users to control water temperature remotely via the Blynk application on a smartphone. This tool can increase and stabilize the water temperature in an aquarium or pond on a certain scale and is very capable of preventing fish from stress resulting from changes in water temperature. This automatic water temperature control system can also provide users with very accurate water temperature information in Celsius units and can save electricity needs and is very easy to use. Keywords: Guppy Ornamental Fish, Internet of Things (IOT), Automatic Water Temperature Control